The sustained influence of metformin therapy on circulating GLP-1 levels in individuals with and without type 2 diabetes - Preiss, D; Dawed, A; Welsh, P; Heggie, A; Jones, A; Dekker, J; Koivula, R; Hansen, T; DIRECT consortium; Stewart, C; Holman, R; Franks, P; et al. (Wiley, 2016)
Aims: Small, short studies suggest metformin influences the glucagon-like peptide (GLP)-1 axis in individuals with and without type 2 diabetes (T2DM). In the Carotid Atherosclerosis: Metformin for insulin ResistAnce (CAMERA) trial (NCT00723307) we investigated whether this effect is sustained and related to changes in glycaemia or weight. In the cross-sectional DIabetes REsearCh on patient straTification (DIRECT) study, we investigated basal and post-meal GLP-1 levels in diabetic patients. Materials and Methods: CAMERA was a double-blinded randomized placebo-controlled trial of metformin in 173 participants without diabetes. Using six-monthly fasted total GLP-1 levels over 18 months, we evaluated metformin's effect on total GLP-1 with repeated-measures and ANCOVA analyses. In DIRECT, we examined active and total fasting and 60-minute post-meal GLP-1 levels in 775 patients recently diagnosed with T2DM treated with metformin or diet, using Student's T-tests and linear regression. Results: In CAMERA, metformin increased total GLP-1 at 6 (+20.7%, [95% confidence intervals 4.7-39.0%]), 12 (+26.7% [10.3-45.6%]) and 18 months (+18.7% [3.8-35.7%]), an overall increase of 23.4% (11.2-36.9%; p < 0.0001) versus placebo. Adjustment for changes in glycaemia and adiposity, individually or combined, did not attenuate this effect. In DIRECT, metformin was associated with higher fasting active (39.1% [21.3-56.4%]) and total GLP-1 (14.1% [1.2-25.9%]) but not post-meal incremental GLP-1. These changes were independent of potential confounders including age, sex, adiposity and HbA1c. Conclusions: In non-diabetic individuals, metformin increases total GLP-1 in a sustained manner and independently of changes in weight or glycaemia. Metformin-treated diabetic patients also have higher fasted GLP-1 independent of weight and glycaemia.